2019
DOI: 10.1177/2054358119856891
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus Consumption Within 1 Hour Prior to Blood Work and Associated Serum Levels of Phosphate, Calcium, and PTH in Adult Patients Receiving Hemodialysis Treatment

Abstract: Background: While dietary intake is known to influence serum markers of chronic kidney disease–mineral and bone disorder (CKD-MBD), the effects of recent food and beverage intake, particularly phosphorus consumption on these serum markers (phosphate, calcium, and parathyroid hormone [PTH]), are unknown in hemodialysis patients. An understanding of these effects could have direct and important implications on the management of CKD-MBD. Objective: To determine whether serum phosphate, calcium, and PTH levels wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…In another study, Mazzetti et al. 23 performed an observational study of serum phosphate levels in routine blood samples from hemodialysis patients, compared patients with and without phosphorus intake during the hour previous to blood sampling, and found serum phosphate to be 0.2 mmol/l higher in the group with phosphorus intake prior to blood sampling. Again, the results are similar to those of our own trial, although the time frame was shorter, and the possible confounders were less well controlled.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study, Mazzetti et al. 23 performed an observational study of serum phosphate levels in routine blood samples from hemodialysis patients, compared patients with and without phosphorus intake during the hour previous to blood sampling, and found serum phosphate to be 0.2 mmol/l higher in the group with phosphorus intake prior to blood sampling. Again, the results are similar to those of our own trial, although the time frame was shorter, and the possible confounders were less well controlled.…”
Section: Discussionmentioning
confidence: 99%
“…The difference in serum phosphate between the 2 meals was just 3%, which is consistent with the results of our own trial. In another study, Mazzetti et al 23 performed an observational study of serum phosphate levels in routine blood samples from hemodialysis patients, compared patients with and without phosphorus intake during the hour previous to blood sampling, and found serum phosphate to be…”
Section: Discussionmentioning
confidence: 99%
“…2,[27][28][29] Specifically, studies have shown that patient adherence to a low phosphorus diet can be increased by consistent education from clinicians. [29][30][31] Another study by Mazzetti and colleagues 32 found that patients who consumed dietary phosphate within 1 h prior to a hemodialysis session experiences alterations in parathyroid hormone levels and had significantly higher serum phosphate values compared to patients who did not consume phosphorus prior to dialysis. 32 These results, combined with our data, illustrate the importance of controlling dietary phosphorus intake to reduce serum phosphate in HD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Finally the blood samples were taken at various time points during the day and included both fasting and nonfasting samples, which may influence serum phosphate levels. 27,28 Future trials should consider a larger sample size with longer follow-up and more uniform timing of samples.…”
Section: Clinical Researchmentioning
confidence: 99%